Prognostic value of liver and kidney function parameters and their correlation with the ratio of urine‐to‐plasma paraquat in patients with paraquat poisoning. Issue 6 (22nd January 2021) - Zhang, Shuangyang; Song, Shuai; Luo, Xuemei; Liu, Jianfeng; Liu, Mouze; Li, Wenqun; Cao, Ting; Li, Nana; Zeng, Cuirong; Zhang, Bikui; Cai, Hualin
Abstract: Acute paraquat poisoning resulting from multiple organ failure usually has a high mortality rate. Liver and kidney, as the key oranges of paraquat detoxification and elimination, their injuries may suppress toxin excretion and enhance the toxicity of paraquat in other organs and worsen the prognosis. Therefore, we intended to explore the prognostic value of liver and kidney function parameters, and further evaluate their correlation with a more stable index urine‐to‐plasma paraquat (urine paraquat concentrations/plasma paraquat concentrations) instead of considering paraquat concentrations in plasma or urine alone. The study included 33 patients with acute paraquat poisoning admitted to four centres in China from January 2018 to December 2019. Seventeen patients (10 male/7 female) survived, whereas 16 patients (7 male/9 female, 48.48%) died from paraquat poisoning. Alanine aminotransferase (ALT) and the blood urea nitrogen (BUN) represent liver and kidney function parameters, respectively. The ratio of urine‐to‐plasma paraquat is negatively correlated with ALT ( r = −0.94, P = 0 .02) and BUN ( r = −0.82, P = 0.03). For receiver operating characteristic curve (ROC) analysis, ALT, BUN and urine‐to‐plasma paraquat have an AUC over 0.80. The study shows that the functional indexes of liver and kidney, as well as the ratio of urine‐to‐plasma paraquat, could be considered for evaluating the extent of organ injury and excretion rate of paraquat.